The Vygotskian perspective and learning: a reflection needed in educational practic (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
Within the educational context, it is considered as one of the highlights learning that nature is an extremely complex process. Vygostskiana perspective suggests considering individual events from a social conception, ie, assuming that reflect the culture and history of a group, hence learning depend on the context in which it develops. You could say that learning is part of education and is the process by which a person acquires the necessary potential to solve different situations. Vygotskian theory considers that higher psychological processes have their origin in social processes making it a benchmark for the understanding of learning and is presented as an argument of this essay. Learning and development is not to be defined in terms of the qualitative leaps and mediation as used, for which you should consider the use of tools and signs. In the Vygotskian approach psychological functions such as memory, attention, perception and thought first appear in primary form then switch to higher forms, ie the natural development produces the elementary functions, while transforming cultural development processes upper elementary processes, thereby achieving the internalization of higher psychological functions. Internalization involves the reconstruction of psychological activity, being a feature of the individual and a process that goes from outside to inside. In this sense, all higher functions originate as a result of the relationships between human beings, so it is important to note that Vygotskian approaches propose to consider individual events as learning from a social conception.
Keywords: education; learning; Vygotsky